2015
DOI: 10.1039/c4cp05073h
|View full text |Cite
|
Sign up to set email alerts
|

Gold and silver nanoparticle monomers are non-SERS-active: a negative experimental study with silica-encapsulated Raman-reporter-coated metal colloids

Abstract: Noble metal nanoparticles (NPs) are the most commonly employed plasmonic substrates in surface-enhanced Raman scattering (SERS) experiments. Computer simulations show that monomers of Ag and Au nanocrystals ("spherical" NPs) do not exhibit a notable plasmonic enhancement, i.e., they are essentially non-SERS-active. However, in experiments, SERS enhanced by spherical NP colloids has been frequently reported. This implies that the monomers do not have strong SERS activity, but detectable enhancement should more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 35 publications
6
75
0
Order By: Relevance
“…Moreover, the corresponding SERS performance of these two nanoparticle morphologies was tested in solutions containing CV at a concentration of 1 μ m (Figure D). This experiment confirmed that SERS of even the highly Raman‐active CV, was below the detection threshold when using Au nanospheres, due to the moderate electromagnetic field enhancement, but SERS signals were clearly observed when anisotropic AuNTs were used. Thus, AuNTs were selected and applied in the subsequent experiments.…”
Section: Resultssupporting
confidence: 77%
“…Moreover, the corresponding SERS performance of these two nanoparticle morphologies was tested in solutions containing CV at a concentration of 1 μ m (Figure D). This experiment confirmed that SERS of even the highly Raman‐active CV, was below the detection threshold when using Au nanospheres, due to the moderate electromagnetic field enhancement, but SERS signals were clearly observed when anisotropic AuNTs were used. Thus, AuNTs were selected and applied in the subsequent experiments.…”
Section: Resultssupporting
confidence: 77%
“…SERS signals are recorded, if our spherical, monodispersed AgNP aggregate and induce plasmon coupling between the NPs resulting in hot spots [107]. SERS signals are not detected in Cinn-AgNP-PI because NP clusters did not form [107]. Cinn-AgNP-PI has the smallest particle size compared to our other compounds TCA-AgNP, TCA-AgNP-PI, and Cinn-AgNP.…”
Section: Discussionmentioning
confidence: 88%
“…The nanocolloidal sample Cinn-AgNP-PI is SERS-inactive ( Figure 9d). SERS signals are recorded, if our spherical, monodispersed AgNP aggregate and induce plasmon coupling between the NPs resulting in hot spots [107]. SERS signals are not detected in Cinn-AgNP-PI because NP clusters did not form [107].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge has recently been mastered for individual spherical particles that were in fact proven to be inactive in terms of Raman enhancement. [24] Based on our simulations, we also consider the SERS effects of SDN as the result of agglomeration and do not assume that the signal arises from individual particles. We also hypothesize that the ability of Nanorice and SDN, namely, to transfer the large particle size into large areas of nearfield enhancement, is an advantage over a spherical approach in case of larger biological structures.…”
Section: Resultsmentioning
confidence: 99%